Beyond αβ/γδ lineage commitment: TCR signal strength regulates γδ T cell maturation and effector fate - Hayes, Sandra M. (2010)
Signaling by the γδ T cell receptor (TCR) is required not only for αβ/γδ lineage commitment but also to activate and elicit effector functions in mature γδ T cells. Notably, at both of these stages, the signal delivered by the γδTCR is more robust than the one delivered by either the preTCR or the αβTCR. Recent studies now provide evidence that signaling by the γδTCR is also required at other stages during γδ T cell development. Remarkably, the strength of the γδTCR signal also plays a role at these other stages, as evidenced by the findings that genetic manipulation of γδTCR signal strength affects γδ T cell maturation and effector fate. In this review, we discuss how a strong TCR signal is a recurring theme in γδ T cell development and activation.